Total phenolic content and antioxidant activity of different streams resulting from pilot-plant processes to obtain Amaranthus mantegazzianus protein concentrates - Castel, María Virginia (2013)
Antioxidant properties of different pilot-plant process streams to obtain Amaranthus mantegazzianus protein concentrates (APC) were evaluated. Conventional process (CP) (alkaline extraction and isoelectric precipitation) and two alternative processes (APs): (1) acid pre-treatment stage combined with isoelectric precipitation and (2) acid pre-treatment stage combined with ultrafiltration were applied at pilot-plant scale to obtain APC. Methanol and water extracts of APC and other fractions obtained in the processes were evaluated by Folin–Ciocalteau method in order to determine total phenolic content and by DPPH radical scavenging activity method to determine antioxidant activity. Acid pre-treatment stage and ultrafiltration caused an effective removal of phenolic compounds yielding on the one hand APC with lower phenolic content than the ones obtained by CP. On the other hand, the acid extract and the whey obtained presented high phenolic content and antioxidant activity and could be used as additives to increased this parameters in food. Finally, evaluated processes could be used to obtain several products (concentrates, whey, extracts) with different phenolic content and antioxidant activity suitable for different applications in food industry.